The effect of positive consumption emotions on customer retention in resorts in Kuching, Sarawak / Muhammad Izzuddin Azman & Edward Empaga Anak - Azman, Muhammad Izzuddin; Anak, Edward Empaga (Faculty of Hotel and Tourism, 2017)
Purpose - To identify how far consumption emotions influenced customer retention. Design/Methodology - Using 150 respondents as the simple random sampling, the results analysed through the frequency tables and Pearson Correlation to test significant relationship. Practical Implication - This research will give much contribution to the hotel and resort industry in Kuching to determine what consumption emotions frequently produced by the guests so that they could further strategized their approach to retain their guests and customers. Originality/Value - This study could change the way the resort management think that the way to retain the guest is deeply connected with the consumption emotions the guest experiencing during their stay at the resort and this study also is a continuous study from the previous researchers. Keywords - Consumption emotions, customer retention.